Pre-Service Teachers’ Digital Competence: A Call for Action - Dolezal, Dominik; Motschnig, Renate; Ambros, Roland (Education sciences, 2025)
In our digital era, pre-service teachers need profound professional digital competences to be able to effectively foster their learners’ digital skills. Studies pointing to a lack of integration of digital competences at secondary schools demonstrate the need for research and action to foster professional digital skills in teacher education. Using a mixed methods approach and based on the DigCompEdu framework, this paper presents the results of a survey comprising 75 questions about students’ capability to teach digital skills, which was answered by 322 advanced pre-service teachers of a large mid-European university. The results of the performed statistical tests and the conducted thematic analysis show that half of the pre-service teachers do not feel sufficiently prepared by their study program to foster digital competence. Students who do not study a STEM subject and students with teaching practice felt significantly less prepared to teach digital skills compared to students who study at least one STEM subject and students without teaching practice, respectively. We conclude that universities should develop and thoughtfully implement a holistic concept to integrate digital skills in the teacher education curriculum to adequately prepare future teachers for the digital era.